PERTANGGUNGJAWABAN PIDANA TERHADAP KEGIATAN MENGEDARKAN PRODUK SEGAR HORTIKULTURA IMPOR YANG TIDAK SESUAI DENGAN STANDAR MUTU DAN/ATAU KEAMANAN PANGAN MENURUT UU NO.13 TAHUN 2013 TENTANG HORTIKULTURA - Kartina Pakpahan; Alvi Syahrin; Mahmud Mulyadi; Dedi Harianto (Universitas Sumatera Utara, 2014)
ABSTRACT Distributing Imported Horticultural Fresh Products to consumers takes a long time or days so that they have to meet the quality standard and/or food security so that they will be safe to be consumed and will not harm consumers health and social welfare. Article 88 Paragraph 1 and 4 of law No.13/2010 on Horticulture regulate responsibility that everyone who distributing imported horticultural fresh products have to meet quality standard and/or food security. Criminal provision expressly stated in the article 128 and 129 of law No.13/2010 on Horticulture, anyone who distributing imported horticultural fresh products that do not meet the quality standard and/or food security required criminally accountable for his actions because it is very harmful to human health both present and future generations. The Criteria of quality standard and/or food security is stipulated in PP No.28/2004 on Food, Quality and Nutrition. Criminal responsibility, applied to perpetrators in criminal act and implemented in the principle of “no crime without any fault”. Fault aspects can be in the form of taking responsibility, willfulness or negligence and excusing liability. The three aspects cannot be separated since they depend on one to another consecutively, an indispensable element for legal subject to be accountable committing the criminal act distributing imported horticultural fresh products that do not meet the quality standard and/or food security. Legal subjects that anyone can be responsible consist of Individuals,Official Empowered to have autority in giving permit, supervision in distributing imported horticultural fresh products, and corporate comprising legal entity and is not a legal entity.